2004
DOI: 10.1152/ajplung.00300.2003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of differentiated human airway epithelium to infection by rhinovirus

Abstract: in vitro studies of the effects of rhinovirus on human airway epithelium have used cells grown under conditions known to produce low levels of differentiation. The relevance of the results to native epithelium is questionable. Here we grew primary cultures of human tracheal or nasal epithelium under three conditions. One condition produced pseudostratified, mucociliary cells virtually indistinguishable from native epithelium. The other two conditions produced undifferentiated squamous cells lacking cilia. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 37 publications
7
95
2
Order By: Relevance
“…By contrast, in mucociliary cultures, 1.6% 6 0.09% of cells were infected, and numbers of foci of infection were almost always one per cell, and never more than three ( Figure 4C). These results are consistent with our previous studies indicating that squamous cultures of human airway epithelium show levels of viral infection (measured from infectious particles released and levels of viral RNA in cell lysates) z100-fold greater than those of mucociliary cultures derived from the same tracheas (9). After treatment of mucociliary cultures with IL-13, numbers of rhinovirus-infected cells increased by z2.5-fold ( Figure 4D).…”
Section: Effects Of Il-13 On Rhinovirus Infectionsupporting
confidence: 93%
See 2 more Smart Citations
“…By contrast, in mucociliary cultures, 1.6% 6 0.09% of cells were infected, and numbers of foci of infection were almost always one per cell, and never more than three ( Figure 4C). These results are consistent with our previous studies indicating that squamous cultures of human airway epithelium show levels of viral infection (measured from infectious particles released and levels of viral RNA in cell lysates) z100-fold greater than those of mucociliary cultures derived from the same tracheas (9). After treatment of mucociliary cultures with IL-13, numbers of rhinovirus-infected cells increased by z2.5-fold ( Figure 4D).…”
Section: Effects Of Il-13 On Rhinovirus Infectionsupporting
confidence: 93%
“…This hypothesis already receives considerable support from our earlier finding of greatly increased levels of infection in squamous cultures (9). However, in cultures grown under conditions that produce mucociliary differentiation, it is well-established that the complexity of the apical membrane increases progressively over the first 28 days in culture (10, 13).…”
Section: Possible Modes Of Action Of Il-13 On Viral Infectionmentioning
confidence: 72%
See 1 more Smart Citation
“…Well-differentiated airway epithelial cells were shown to be more resistant to HRV infection than the same cells in undifferentiated monolayers (45). However, a recent study reported that various types of differentiated bronchial epithelial cells differ in their susceptibility to RV infection (46).…”
Section: Discussionmentioning
confidence: 99%
“…For RV1B infection, a multiplicity of infection (MOI) of 1 was used by adding a volume of RV1B that provided 1 Ï« 10 6 plaqueforming units (PFU) to 1 Ï« 10 6 respiratory tract epithelial cells. This protocol was based on previously published techniques (20).…”
Section: Cellmentioning
confidence: 99%